2019
DOI: 10.4254/wjh.v11.i3.305
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative immunonutrition in patients undergoing liver resection: A prospective randomized trial

Abstract: BACKGROUND Preoperative supplementation with immunonutrients, including arginine and n-3 fatty acids, has been shown in a number of systematic reviews to reduce infectious complications in patients who have undergone gastrointestinal surgery. Limited information, however, is available on the benefits of nutritional supplementation enriched with arginine and n-3 fatty acids in patients undergoing liver resection. AIM To evaluate the effects of preoperative nutritional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…However, these benefits cannot be exclusively attributed to EPA because the oral supplementation was also enriched with arginine and nucleotides. A similar approach but with controversial results was conducted by Russell et al Indeed, any benefit of preoperative immunonutrition was reported with arginine and n-3 fatty acids [69]. In a retrospective study reported by Kamo et al, liver recipients suffering from infection after LT were submitted to enteral immunonutrition enriched with nucleotides, arginine and omega-3 fatty acids, and hydrolyzed whey peptide (HWP) (an immunonutritional liquid).…”
Section: Fatty Acids Arginine and Nucleotidesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, these benefits cannot be exclusively attributed to EPA because the oral supplementation was also enriched with arginine and nucleotides. A similar approach but with controversial results was conducted by Russell et al Indeed, any benefit of preoperative immunonutrition was reported with arginine and n-3 fatty acids [69]. In a retrospective study reported by Kamo et al, liver recipients suffering from infection after LT were submitted to enteral immunonutrition enriched with nucleotides, arginine and omega-3 fatty acids, and hydrolyzed whey peptide (HWP) (an immunonutritional liquid).…”
Section: Fatty Acids Arginine and Nucleotidesmentioning
confidence: 96%
“…In experimental and clinical studies performed in animals and humans, fatty acids, arginine, and nucleotides have shown the ability to modulate immune and inflammatory responses [18,69]. These nutrients, among others, have been labeled as pharmaconutrients [18].…”
Section: Fatty Acids Arginine and Nucleotidesmentioning
confidence: 99%
“…Whole 45 studies were eligible for further full-text screening, and 36 studies were excluded because they did not meet the inclusion criteria: 7 were not RCTs, 10 were systematic reviews, 5 were letters, and 14 articles lacked the related data. Finally, 9 articles were included in the analysis [21][22][23][24][25][26][27][28][29]. A flow diagram of the search strategy is presented in Figure 1.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The bias risk of the included studies was assessed using the Cochrane Collaboration risk of bias tool. Seven articles [22,23,[25][26][27][28][29] reported the methods of random sequence generation, 4 studies [22,23,25,27] performed allocation concealment, 8 studies [22][23][24][25][26][27][28][29] described the blinding of participants and personnel, and 6 studies [22,23,25,[27][28][29] considered blinding of outcome assessment. Seven studies [22][23][24][26][27][28][29] reported incomplete outcome data, while the remaining 2 trials [21,25] were considered to have a high risk of attrition bias because of the high dropout rate.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation